THE DURATION OF CARS DEPOSITION AND THE FACTORS THAT AFFECT IT - Zhuravel, V. V. (Science and Transport Progress, 2008)
A type of regression equations is determined, which adequately describe correlation between the error of braking of sets of cars and the factors affecting mean duration of reining in on one processed car. The solution for problem of determination of mean duration of reining in on one train depending on the weight category of cars in the stream being processed is offered.